Assessing the effectiveness of multistakeholder platforms: Agricultural and rural management councils in the Democratic Republic of the Congo - Badibanga, Thaddée; Ragasa, Catherine; Ulimwengu, John M. (International Food Policy Research Institute, 2013)
This paper analyzes the effectiveness of local-level (territory) multistakeholder platforms using data from 55 CARGs in 23 randomly selected territories in three provinces (Bandundu, Bas-Congo, and Kinshasa) of the DRC. The first CARG was established in 2008, and the survey was conducted three years later, from August to October 2011.